Short term effect of spinal mobilization with movement (MWM) on pulmonary functions in nonsmokers with thoracic hyperkyphosis: a randomized single-blinded controlled trial - El Gendy, Mohamed H.; Mohamed, Shaimaa R; Taman, Saher E; Hussein, Hisham M.; Abu El Kasem, Shimaa T. (The Journal of manual & manipulative therapy, 2023)
To investigate the effect of mobilization with movement (MWM) on pulmonary functions in subjects with thoracic hyperkyphosis. This randomized single-blinded controlled trial included a sample of 50 subjects (age 18 − 25 years old) with thoracic hyperkyphosis. Subjects were randomly allocated into two groups; the Real MWM group (n = 25) which received thoracic MWM plus standard postural correction exercises, and the Sham MWM group (n = 25) which received sham MWM plus standard postural correction exercises. Digital X-ray and handheld spirometer were used to measure selected pulmonary function tests (FVC, FEV1/FVC ratio, MVV) respectively. Within-group comparisons demonstrated a statistically significant improvement in all outcome measures in both groups. The between-group comparisons demonstrated significant improvement in the MWM compared to the Sham group regarding the value of FVC, FEV1/FVC ratio, and MVV (P < .05). In young adults with thoracic hyperkyphosis, MWM plus postural exercise produces better improvements in FVC, FEV1, FEV1/FVC, and MVV compared to sham MWM plus postural exercise.